2011
DOI: 10.1016/j.clim.2011.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated alteration in naive and memory Th17 cell response in humans

Abstract: Th17 cells produce IL-17 that plays an important role in host defense. However, little is known about whether aging affects human Th17 cells. Here we demonstrated that healthy elderly people (age≥65) had a decreased frequency of IL-17-producing cells in memory CD4+ T cells compared to healthy young people (age≤40) while both groups had similar frequencies of IFN-γ-producing cells in the same memory cell subset as measured by flow cytometry. In contrast, the healthy elderly had increased differentiation of IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 33 publications
9
44
1
Order By: Relevance
“…Similar to previous studies, we observed that Th1, Th2 and Th17 cell numbers are either retained or decreased in the elderly (Alberti et al, 2006;Karanfilov et al, 1999;Lee et al, 2011). Both in young and aged individuals, these T eff subsets primarily resided within the memory CD4+ T cell compartment.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar to previous studies, we observed that Th1, Th2 and Th17 cell numbers are either retained or decreased in the elderly (Alberti et al, 2006;Karanfilov et al, 1999;Lee et al, 2011). Both in young and aged individuals, these T eff subsets primarily resided within the memory CD4+ T cell compartment.…”
Section: Discussionsupporting
confidence: 90%
“…In the latter study, however, the number of Th17 cells may have been overestimated, as Th17 cells were solely identified by expression of the IL-23 receptor, which is also expressed by cells other than Th17 cells (Parham et al, 2002). We and others identified Th17 cells by expression of their hallmark cytokine IL-17 and found decreased numbers of these cells in elderly individuals (Lee et al, 2011). Our data therefore indicate that aging in healthy elderly substantially tilts the T reg /Th17 balance towards T reg cells.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Elevated frequencies of Th17 cells have been observed in old mice and humans 21,22 . More importantly, Th17 cells have been linked to critical pathways in allograft rejection 23 .…”
Section: Resultsmentioning
confidence: 99%
“…One study concluded upon the oscillatory nature of T reg numbers through life, with peaks in adolescence and in over 60 year olds [8]. A recent study in T h 17 cells with age showed a small decrease in the frequency of T h 17 cells in the CD4 + memory population in elderly donors relative to young [9]. However, for the balance between T reg s and T h 17 cells, there is currently no published literature.…”
Section: The Need For Balance: T H 17s and T Reg S Throughout The Lifmentioning
confidence: 99%